The decision to join Special Olympics: Parents' perspectives - Goodwin, D. L.; Fitzpatrick, D. A.; Thurmeier, R.; Hall, G. (Adapted Physical Activity Quarterly, 2006)
This phenomenological study explored the decision-making experience of parents whose children joined Special Olympics programs. The experiences of 16 families with children 10-22 years old were gathered through interviews, artifacts, and field notes. Three themes emerged from the thematic analysis (a) thoughtful instruction, (b) finding the fit, and (c) security of acceptance. Parents sought instructors who were interested in building relationships with their children and creating anxiety-free instructional environments for them. A good program fit occurred when instructors had expectations for motor skill development and increased independence. Parents also preferred environments that encouraged meaningful peer interactions. The findings were interpreted within the context of self-determination theory.